The day-of-the-week effect revisited: An alternative testing approach - Raimund Alt; Ines Fortin; Simon Weinberger (Institute for Advanced Studies (IHS), 2002)
This paper questions traditional approaches for testing the day-of-the-week effect on stock returns. We propose an alternative approach based on the closure test principle introduced by Marcus, Peritz and Gabriel (1976), which has become very popular in Biometrics and Medical Statistics. We test all pairwise comparisons of daily expected stock returns, while the probability of committing any type I error is always kept smaller than or equal to some prespecified level a for each combination of true null hypotheses. We confirm day-of-theweek effects for the S&P 500, the FTSE 30 and the DAX 30 found in earlier studies, but find no evidence for the 1990's.
Keywords: C12; C20; G14; 330; day-of-the-week effect; multiple hypotheses testing; multiple comparisons; closed test procedures; multiple level a test; Kapitalertrag; Börsenkurs; Kalendereffekt; Statistischer Test; Schätzung; Aktienindex; Deutschland; USA; Großbritannien